A new variant of the electromagnetic field theory of consciousness: approaches to empirical confirmation - Strupp, Wolfram (Frontiers in Neurology, 2024)
There are various electromagnetic (EM) field theories of consciousness. They postulate an epineural EM field which, due to its binding properties, unifies the different neuronal information differences originating from various sensory and cognitive processes. Only through a real physical integration in space within this field could phenomenal consciousness arise. This would solve the binding problem mentioned in the philosophy of mind. On closer inspection, the electromagnetic interaction not only provides an explanation for the integrative property of the EM field, but also for the necessary differentiating contrasts of information. This article will take a closer look at the physical properties of a postulated EM field. It will also show how the problem of qualia in connection with emergentism could be solved by a new variant of EM field theory. If it can be clearly demonstrated that the postulated epineural EM field plays a decisive role in the origin of consciousness in addition to neuronal “wired” information processing, this also leaves less room for metaphysical assumptions that attempt to solve the binding problem. In experiments to prove the postulated epineural EM field by means of external electromagnetic manipulations, it can never be ruled out that these also have a direct effect on the “wired” neuronal signal processing. Therefore, on the way to proving the EM field theory of consciousness, an experimental method is needed that must ensure that external manipulations only affect the extensions of the EM field without directly influencing the neuronal network. A method will be discussed here that works with the shielding of EM fields instead of external electromagnetic stimuli.